2021
DOI: 10.3389/fpls.2021.684671
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Trait Loci Mapping of Adult Plant and Seedling Resistance to Stripe Rust (Puccinia striiformis Westend.) in a Multiparent Advanced Generation Intercross Wheat Population

Abstract: Stripe rust caused by the biotrophic fungus Puccinia striiformis Westend. is one of the most important diseases of wheat worldwide, causing high yield and quality losses. Growing resistant cultivars is the most efficient way to control stripe rust, both economically and ecologically. Known resistance genes are already present in numerous cultivars worldwide. However, their effectiveness is limited to certain races within a rust population and the emergence of stripe rust races being virulent against common res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
9
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 117 publications
(193 reference statements)
5
9
2
Order By: Relevance
“…Our study also detected four loci associated with stripe rust resistance on chromosomes 2BS, 6AL, 7AL, and 7BL (Table 4), which could correspond to QTL previously reported by Prins et al (2011), Vazquez et al (2012, Rosewarne et al (2012), Agenbag et al (2014), Miedaner et al (2019), Beukert et al (2020a), Jia et al (2020), and Rollar et al (2021. Of these, QTL on chromosomes 2BS and 6AL were identified in German plant materials including a winter wheat diversity panel (Miedaner et al 2019), a hybrid wheat panel (Beukert et al 2020a), and a multiparental population (Rollar et al 2021). Interestingly, these two QTL were not reported in the worldwide collections of hexaploid spring (Maccaferri et al 2015) and winter wheat (Bulli et al 2016), suggesting that they were specifically enriched through European breeding activities.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our study also detected four loci associated with stripe rust resistance on chromosomes 2BS, 6AL, 7AL, and 7BL (Table 4), which could correspond to QTL previously reported by Prins et al (2011), Vazquez et al (2012, Rosewarne et al (2012), Agenbag et al (2014), Miedaner et al (2019), Beukert et al (2020a), Jia et al (2020), and Rollar et al (2021. Of these, QTL on chromosomes 2BS and 6AL were identified in German plant materials including a winter wheat diversity panel (Miedaner et al 2019), a hybrid wheat panel (Beukert et al 2020a), and a multiparental population (Rollar et al 2021). Interestingly, these two QTL were not reported in the worldwide collections of hexaploid spring (Maccaferri et al 2015) and winter wheat (Bulli et al 2016), suggesting that they were specifically enriched through European breeding activities.…”
Section: Discussionsupporting
confidence: 85%
“…The chromosomal positions of several stripe rust resistance genes and quantitative trait loci (QTL) were determined using classical mapping approaches (Tsomin et al 1990; Bariana and McIntosh 1993;Michelmore et al 1991;Xu et al 2008;Edae et al 2016;Gessese et al 2021) and, more recently, using genome-wide association studies (GWAS) (Bouvet et al 2021;Rollar et al 2021). To complement traditional QTL mapping, GWAS combined with high-density SNP genotyping have been successfully used as powerful tools for discovery of stripe rust resistance loci in a global collection of winter wheat accessions (Bulli et al 2016), spring wheat landraces (Kankwatsa et al 2017), diverse Indian spring wheat cultivars (Kumar et al 2020), U.S. winter wheat cultivars and breeding lines (Mu et al 2020), elite wheats of the International Maize and Wheat Improvement Center (CIMMYT) (Juliana et al 2018), European winter wheat (Miedaner et al 2019), and modern Chinese wheat (Jia et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The 6 SNP loci (Table 1) associated with the severity of yellow rust infection (based on the average of infection type in the experiments) represented QTL with small effects (R 2 less than 10%). Such low-effect QTL for resistance to yellow rust at the seedling stage were also identified in the U.S. elite spring wheat lines [19], the German MAGIC winter wheat population [20], and a Chinese wheat landrace association panel [5]. About 50% of the lines in our study showed moderate resistance to both Warrior (-) races at the seedling stage, indicating the presence of a relatively large number of genes with a moderate effect.…”
Section: Discussionsupporting
confidence: 67%
“…While several studies [5,15,19,20] have identified similar QTL controlling resistance to yellow rust at both seedling and adult stages, suggesting the presence of resistance genes for all stages, others [39,40], including our study, have not found common QTL or representative SNP loci between these two developmental stages. This divergence may be because many other loci contribute more to resistance in the fields in response to a population of pathotypes, while in seedling tests there is only a limited response to a few races.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation